Influência do alagamento na vegetação arbórea em uma planície inundável no Médio São Francisco, MG, Brasil - Miranda, Kaline Fernandes (2016)
Flood forests are vegetation subject to seasonal floods. Situated in flood plains, they are systems under continuous changes due to the pulses of flooding, always alternating following the watercourse. However, there are little publications that report the floristic structure in flood plains, especially in Southeastern Brazil. This study aimed at characterizing the composition, structure and diversity of the arboreal community flooding gradient, comparing them with the non-flood adjacent formations, at the mouth of the River Paracatu in River São Francisco, Minas Gerais, Brazil. For the structural survey of the arboreal community, we used the plot method, installed on both sides of River Paracaty. The individuals were identified at the species level. The circumference measures were gauged with a measuring tape. Individuals with more than one stem (support) at 1.30 m of the soil were included in the registry, provided the square root of the square sum of the stems be superior or equal to the inclusion criterion. We sampled 1,276 individuals belonging to 85 species, of 32 families. The Shannon Index (H`) regarding the total sampling was of 3.40 ind.nat, with Pielou equability index (J`) of 0.76. In terms of species importance, the six most important species were comprised of 46% of the total index of importance value. By means of similarity analysis, it was possible to verify the grouping of species along the geoforms, demonstrating the substitution of species along habitats, resulting in the temporal difference of the flooding in the environments. In conclusion, the flooding regimes, frequency and intensity determine the ecology of the river plains.